Civilized Congress: Election and Organization of the 48th Muktamar of Muhammadiyah in Solo, Indonesia - Ahmad Najib Burhani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
The theme of this 48th Congress of Muhammadiyah is “Memajukan Indonesia, Mencerahkan Semesta” (Advancing Indonesia, Enlightening the Universe). What was happening there accurately reflected and implemented this theme. From the process of election, side events of the congress, to the activities of participants correctly called “penggembira” (cheerful and happy supporters).After three times rescheduling and two years of delay, Muhammadiyah successfully organized its Muktamar or Congress in Surakarta, Central Java, on 18-20 November 2022. Muktamar is actually a five-yearly event and the previous congress, the 47th congress, was held in Makassar in 2015. Due to the Covid-19 pandemic that has made gathering of large number of people impossible, Muhammadiyah decided to extend the mandate of the chairmen and all its structure, at first, until 2021 and then extended again until 2022. Muhammadiyah had tried to have a virtual congress or hybrid and had developed technological device for that, but at the end the congress was organized fully offline.